The influence of menstrual cycle phases on postconcussion outcomes and symptom reporting: a scoping review - Carr, G.; Fleddermann, M.-T. (Scandinavian Journal of Medicine & Science in Sports, 2025)
Concussion is common in sports and often shows sex-based differences in symptom severity and recovery, with female athletes experiencing more severe, prolonged symptoms. Hormonal changes during the menstrual cycle may play a role in concussion, but research on this topic has been limited. Therefore, this scoping review aimed to investigate whether the menstrual cycle phase—both at the time of injury and after injury—influences postconcussion outcomes and symptom reporting, and whether menstrual cycle phases influence baseline assessments in the absence of injury. This review was conducted according to PRISMA-ScR guidelines and included studies on the influence of menstrual cycle phases on concussion-related outcomes retrieved from PubMed, Web of Science, and BISp-Surf databases. Five studies involving 774 females identified variations in symptom severity and health outcomes across menstrual cycle phases, with differences between the luteal and follicular phases. Findings suggest that hormonal fluctuations, particularly the withdrawal of elevated progesterone during the luteal phase, may contribute to worse postconcussion symptoms and outcomes, with these hormone levels at the time of injury emerging as a potential predictor of recovery severity. Baseline assessment evaluations should account for menstrual cycle phase, because this influences symptom variability and severity. This review underscores the importance of incorporating menstrual cycle phases into concussion management strategies in order to enhance diagnostic accuracy and recovery approaches for female athletes. Addressing these hormonal influences can advance both research and practice in the management of concussion.